The Effect of YouTube Learning Videos on Student Learning Outcomes in Block Programming Subjects - Hijrah Sakinah; Galih Yudha Saputra; Ari Prayogo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze the effect of using YouTube videos as an additional learning resource on student learning outcomes in Block Programming. The research method used a quasi-experiment with two groups, namely class 7E as the control group and class 7F as the experimental group. The sample was selected from two classes with the lowest daily test scores among all seventh-grade students at SMP Negeri 2 Tenggarong Seberang. The independent variable in this study was the use of YouTube media, while the dependent variable was student learning outcomes. Normality and homogeneity tests showed that the data met the requirements for further analysis. The results showed that the average post-test score of the experimental class that used YouTube media was 78, higher than the control class, which had an average score of 74. The hypothesis test results using SPSS version 26 obtained a significance value of 0.041 < 0.05, so Hₐ was accepted and H₀ was rejected. Thus, this study concluded that the use of YouTube videos had a significant effect on improving student learning outcomes in Block Programming material